An autonomous wireless sensor network deployment system using mobile robots for human existence detection in case of disasters - Tuna, Gurkan; Gungor, V. Cagri; Gulez, Kayhan (ELSEVIER, 2014)
This paper presents a novel approach of using autonomous mobile robots to deploy a Wireless Sensor Network (WSN) for human existence detection in case of disasters. During WSN deployment, mobile robots perform cooperative Simultaneous Localization and Mapping (SLAM) and communicate over the WSN. The proposed system has important advantages over a human-assisted system, including autonomous deployment, aggregated intelligence, and flexibility. However, the realization of these envisaged gains depends on communication and coordination capabilities of the system. In this study, the advantages of an autonomous WSN deployment system by mobile robots, design principles and implementation related issues have been explained. In addition, simulation studies have been performed to show the effectiveness of the proposed approach considering WSN coverage, coordination strategies, and SLAM perspectives. Overall, this paper addresses the advantages of using multiple robots for WSN deployment in terms of cooperative exploration and cooperative SLAM, the benefit of simultaneously deploying wireless sensor nodes during the exploration of an unknown deployment zone and the use of WSN-based communication as an alternative communication method during exploration. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Wireless sensor networks; Human existence detection; Cooperative Simultaneous Localization and Mapping (SLAM); Map merging; Sensor node deployment strategies; REAL-TIME; SIMULTANEOUS LOCALIZATION; LIFETIME; SLAM; Computer Science; Telecommunications